2018
DOI: 10.20956/icon.v2i1.3579
|View full text |Cite
|
Sign up to set email alerts
|

Related Factors of Response Time in Handling Head Injury in Emergency Unit of PROF.DR.H.M.ANWAR Makkatutu Bantaeng General Hospital

Abstract: Introduction: The mechanisms of nurse response time in handling head injury patients has an important role on the safety and viability of patients in reference to the rules of “safety and time saving is life saving”. The purpose of the study: This study aims to identify factors that related to the response time in handling head injury patient in emergency department (ED) and to determine the most related factor  to the response time. Method: This study was an observation design and using cross sectional approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Several factors influence this condition.Several things, including the number of staff, facilities, and infrastructure, as well as the knowledge or experience of nurses, affect the response time (Shoja et al, 2020;Suwarno et al, 2020). There is also a relationship between education level and response time (Mudatsir et al, 2018). However, other studies have found no association between education and response time (Ashra & Amalia, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…Several factors influence this condition.Several things, including the number of staff, facilities, and infrastructure, as well as the knowledge or experience of nurses, affect the response time (Shoja et al, 2020;Suwarno et al, 2020). There is also a relationship between education level and response time (Mudatsir et al, 2018). However, other studies have found no association between education and response time (Ashra & Amalia, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…Penelitian ini sejalan dengan penelitian yang dilakukan oleh Mudatsir et al, (2017) dengan judul "Related Factors of Response Time In Handling Head Injury In Emergency" didapatkan hasil ada hubungan pelatihan kegawatdaruratan yang diikuti Perawat dengan waktu tanggap penanganan pasien cedera kepala. Penelitian ini juga didukung oleh penelitian Yulia, (2022) yang mana didapatkan hasil uji statistik dengan uji Fisher Test diperoleh nilai p = 0,005 < 0,05.…”
Section: Pembahasan Hubungan Pelatihan Dengan Response Time Perawatunclassified